Berlin contemporary : architecture and politics after 1990 - Walker, Julia (Julia W.) (New York : Bloomsbury Visual Arts, 2022)
"Berlin Contemporary examines the architecture and urban planning of reunified Berlin, and reveals how its iconic new government structures embody the unsettled contradictions that animate contemporary architecture"--
Introduction: Berlin, the Contemporary Capital -- Bridging and Breaking--Master Planning the Spreebogen -- The Reichstag's New Lightness of Being -- Monumental Modernism--The Chancellery as Future Ruin -- Palaces of Doubt -- Conclusion: No One Intends To Open an Airport.
Includes bibliographical references and index.
Keywords: Public buildings -- Germany -- Berlin; Architecture and society -- Germany -- Berlin -- History -- 20th century; Architecture and society -- Germany -- Berlin -- History -- 21st century; City planning -- Germany -- Berlin -- History -- 20th century; City planning -- Germany -- Berlin -- History -- 21st century; Germany -- Capital and capitol; Berlin (Germany) -- Buildings, structures, etc; Print books